Motion Arrested (Wesleyan University Press, 1982)
A collection of reviews by eminent critic of the Boston Evening Transcript, H.T. Parker, edited and with an introduction by former dancer Olive Holmes-whose selection brings thirty years of dance to life. Includes reviews on many important dance figures like Ruth St. Denis and Isadora Duncan, forming a unique record of the period of the American discovery of dance.